Addressing challenges in the treatment of tuberculosis and tuberculosis meningitis: a pharmacometric approach - Abdelgawad, Noha (Department of Medicine, 2025)
Tuberculosis (TB) is the primary cause of death from a single infectious agent worldwide. During the coronavirus disease (COVID-19) pandemic, TB briefly fell to second place, but it has now regained its position as the top infectious killer. It is caused by Mycobacterium tuberculosis and mainly targets the lungs, but it can spread to other tissues, which can result in TBM, a more severe and often fatal form that affects the central nervous system (CNS), particularly the meninges. In South Africa, TB and TBM burdens are particularly high due to factors such as high HIV prevalence. The treatment of TB and TBM presents significant challenges. Firstly, it typically involves numerous antibiotics taken over several months that may cause serious adverse effects, leading to poor adherence, which can result in treatment failure or the development of drug resistance. Secondly, TB management in hospitalised patients becomes more difficult since they often face more advanced stages of the infection, as well as physiological changes that could impact the pharmacokinetics of anti-TB drugs. Lastly, TBM treatment is further complicated by limited antitubercular drug penetration into the CNS due to its protective barriers, disease-related physiological changes to these barriers and neurological complications. A further challenge is the treatment of special populations, such as children, where unique pharmacokinetic and formulation considerations may complicate management. In this thesis, we use pharmacometric modelling and simulation approaches to tackle some of the obstacles encountered in TB and TBM treatment. Firstly, we demonstrate how pharmacometric approaches can x be useful in monitoring adherence to TB drugs. Secondly, we investigated the differences in the pharmacokinetics of rifampicin, isoniazid, and pyrazinamide in hospitalised patients, who are more severely ill, compared to outpatients. Although we found slower rifampicin absorption and higher between-subject variability in pyrazinamide clearance in hospitalised patients compared to outpatients, we did not identify any changes in pharmacokinetics that are expected to be of clinical significance. It is reassuring that hospitalized patients do not seem to have lower antitubercular drug exposures than outpatients. Thirdly, in South African children diagnosed with definite or probable TBM, we estimated the extent of rifampicin's lumbar and ventricular cerebrospinal fluid (CSF) penetration to be ~5% of plasma. We were also able to use the microdialysis technique to obtain brain extracellular fluid samples to present a proof-of-concept that rifampicin enters the brain tissue. These results show that the microdialysis technique is a promising way to study site-of-disease pharmacokinetics in TBM and pave the way for optimisation of TBM regimens. Lastly, in South African adults with TBM/HIV, we described the plasma and CSF pharmacokinetics of standard and high-dose (10 and 35 mg/kg) rifampicin and linezolid. We estimated lumbar CSF penetration of rifampicin to be ~5%, which is in line with the results of our study in children. Linezolid CSF penetration increased with higher CSF total protein levels, peaking at 37%. Neither the duration of rifampicin co treatment nor the dose level (standard 10 mg/kg vs high 35 mg/kg) was found to affect xi linezolid pharmacokinetics. Our findings endorse the continued evaluation of high dose rifampicin (35 mg/kg) and linezolid for optimizing TBM treatment regimens. To conclude, thanks to pharmacometric approaches, we could address some of the challenges encountered in TB treatment, namely, using modelling and simulation to monitor drug adherence, understanding the pharmacokinetics of the first-line anti TB drugs in hospitalised TB patients, and investigating CNS pharmacokinetics of rifampicin and linezolid in TBM patients.